Efektivitas Penggunaan Aplikasi Pendidikan Digital dalam Meningkatkan Kemampuan Literasi Anak Usia Dini TK AL-FIKR Desa Morome Kecamatan Konda - Aris Suziman; Sri Jumiaty Permatasari; Itsnain Alfajri Husain (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to evaluate the effectiveness of using digital educational applications to improve early childhood literacy skills at TK AL-FIKR, Desa Morome, Kecamatan Konda. The method used in this study is a qualitative approach with a case study design. Data was collected through direct observation, interviews with teachers and parents, and documentation of children's literacy development over six weeks of using the digital educational application. The results of the study show that the digital educational application, which combines educational games, illustrated stories, and writing exercises, has a significant positive impact on children's engagement in literacy learning. Children who used the application were more active, enthusiastic, and able to recognize letters, read simple words, write sentences, and speak more clearly. Teachers and parents also reported an increase in children's interest in learning after using the application, as well as improvements in their speaking and writing abilities. However, supervision from teachers and parents is crucial to ensure the application is used effectively and remains focused on the learning objectives. The study concludes that digital educational applications are an effective tool in improving early childhood literacy skills, with full support from teachers and parents. These applications can be a valuable alternative in literacy learning in the digital age.